1982
DOI: 10.1002/esp.3290070112
|View full text |Cite
|
Sign up to set email alerts
|

Flow variability and hillslope hydrology

Abstract: Examination of spatial variability of streamflow in headwater areas can provide important insight about factors that influence hillslope hydrology. Detailed observations of variations in stream channel input, based on a tracer experiment, indicate that topography alone cannot explain flow variability. However, determination of changes in channel input on a small spatial scale can provide valuable clues to factors, such as structural geology that control subsurface flows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…In this study, we aimed to identify the dominant watershed properties that influence the timing and magnitude of stream flow and how this scales from the reach to the entire watershed. Common elements that have been shown to influence spatiotemporal variability in streamflow include topographic characteristics such as contributing area [e.g., Anderson and Burt , ; Beven and Kirkby , ; Wood et al ., ; Jencso et al ., ], vegetation [ Rodriguez‐Iturbe and Porporato , ; Nippgen et al ., ], subsurface characteristics such as bedrock structure [e.g., Huff et al ., ; Freer et al ., ; Uchida et al ., ], and differences in valley bottom–stream geomorphology [ Harvey and Bencala , ; Ward et al ., ; Wondzell , ] that can promote bi‐directional exchanges (gains and losses) of water between streams and valley bottom systems. However, we have not yet resolved how channel and valley hydrologic exchange can modulate hillslope contributions to streams or how this leads to differences in watershed scale discharge dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to identify the dominant watershed properties that influence the timing and magnitude of stream flow and how this scales from the reach to the entire watershed. Common elements that have been shown to influence spatiotemporal variability in streamflow include topographic characteristics such as contributing area [e.g., Anderson and Burt , ; Beven and Kirkby , ; Wood et al ., ; Jencso et al ., ], vegetation [ Rodriguez‐Iturbe and Porporato , ; Nippgen et al ., ], subsurface characteristics such as bedrock structure [e.g., Huff et al ., ; Freer et al ., ; Uchida et al ., ], and differences in valley bottom–stream geomorphology [ Harvey and Bencala , ; Ward et al ., ; Wondzell , ] that can promote bi‐directional exchanges (gains and losses) of water between streams and valley bottom systems. However, we have not yet resolved how channel and valley hydrologic exchange can modulate hillslope contributions to streams or how this leads to differences in watershed scale discharge dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Subsurface water storage areas cannot be easily derived from surficial and geological data (e.g., McClymont et al, ; Muir et al, ) although previous studies found that it is possible to some extent to determine contributions to stream discharge based on topography (e.g., Anderson & Burt, ). Other reasons might be significant inflows from bedrock exfiltration (Holbrook et al, ; Huff, O'Neill, Emanuel, Elwood, & Newbold, ) or because changes in streamflow occur due to a combination of both losses and gains (Covino, McGlynn, & Mallard, ; Mallard, McGlynn, & Covino, ). We did not specifically measure the losses, but discharge decreased between X1 and D4 within measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of applying to describe subsurface flow in complex hillslopes stem from the fact that it does not account for the three‐dimensional soil mantle in which the flow process takes place. Studies reporting observations of the spatial variability of subsurface flow [e.g., Anderson and Burt , 1978; Huff et al , 1982; McDonnell , 1990; Woods et al , 1997] identified topography as a significant control. The geometry of the hillslope therefore needs to be taken into account to fully capture the dynamics of subsurface flow along complex hillslopes.…”
Section: Hillslope‐storage Boussinesq Modelmentioning
confidence: 99%